Robotic-Assisted Peripheral Nerve Surgery: A Systematic Review - Chen, Lisa Wen-Yu; Goh, Mei; Goh, Raymond; Chao, Yin-Kai; Huang, Jung-Ju; Kuo, Wen-Ling; Sung, Cheyenne Wei-Hsuan; Chuieng-Yi Lu, Johnny; Chuang, David Chwei-Chin; Chang, Tommy Nai-Jen (Journal of Reconstructive Microsurgery, 2021)
Background Robotic-assisted techniques are a tremendous revolution in modern surgery, and the advantages and indications were well discussed in different specialties. However, the use of robotic technique in plastic and reconstructive surgery is still very limited, especially in the field of peripheral nerve reconstruction. This study aims to identify current clinical applications for peripheral nerve reconstruction, and to evaluate the advantages and disadvantages to establish potential uses in the future.Methods A review was conducted in the literatures from PubMed focusing on currently published robotic peripheral nerve intervention techniques. Eligible studies included related animal model, cadaveric and human studies. Reviews on robotic microsurgical technique unrelated to peripheral nerve intervention and non-English articles were excluded. The differences of wound assessment and nerve management between robotic-assisted and conventional approach were compared.Results Total 19 studies including preclinical experimental researches and clinical reports were listed and classified into brachial plexus reconstruction, peripheral nerve tumors management, peripheral nerve decompression or repair, peripheral nerve harvesting, and sympathetic trunk reconstruction. There were three animal studies, four cadaveric studies, eight clinical series, and four studies demonstrating clinical, animal, or cadaveric studies simultaneously. In total 53 clinical cases, only 20 (37.7%) cases were successfully approached with minimal invasive and intervened robotically; 17 (32.1%) cases underwent conventional approach and the nerves were intervened robotically; 12 (22.6%) cases converted to open approach but still intervened the nerve by robot; and 4 (7.5%) cases failed to approach robotically and converted to open surgery entirely.Conclusion Robotic-assisted surgery is still in the early stage in peripheral nerve surgery. We believe the use of the robotic system in this field will develop to become popular in the future, especially in the fields that need cooperation with other specialties to provide the solutions for challenging circumstances.
Keywords: telerobotic; robot; peripheral nerve reconstruction